Diagnostic Approach in Impotence and Imaging Modalities - Medih Celiktas (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2015)
Penile erection results from a complex interplay between central nerveus system and local factors. Several aspects of these interactions have been the subject of many reviews. Nocturnal penile tumescence (NPT) monitoring is the best single non-invasive examination to differentiate organic from psychogenic impotence. Angiography and pharmaco-cevernosometry are accepted as gold standard modalities in the assesment of vasculojenic impotence. Recently color Doppler sonography made the detection of vessels easier and the correction of the Doppler angle more accurate, resulting in more rapid and accurate acquisition of data. [Cukurova Med J 2015; 40(2.000): 208-211]